The Endosymbiotic Coral Algae Symbiodiniaceae Are Sensitive to a Sensory Pollutant: Artificial Light at Night, ALAN - Ayalon, Inbal; Benichou, Jennifer I. C.; Avisar, Dror; Levy, Oren (Frontiers in Physiology, 2021)
Artificial Light at Night, ALAN, is a major emerging issue in biodiversity conservation, which can negatively impact both terrestrial and marine environments. Therefore, it should be taken into serious consideration in strategic planning for urban development. While the lion's share of research has dealt with terrestrial organisms, only a handful of studies have focused on the marine milieu. To determine if ALAN impacts the coral reef symbiotic algae, that are fundamental for sustainable coral reefs, we conducted a short experiment over a period of one month by illuminating isolated Symbiodiniaceae cell cultures from the genera Cladocopium (formerly Clade C) and Durusdinium (formerly Clade D) with LED light. Cell cultures were exposed nightly to ALAN levels of 0.15 µmol quanta m-2 s-1 ( 4-5 lux) with three light spectra: blue, yellow and white. Our findings showed that even in very low levels of light at night, the photo-physiology of the algae's Electron Transport Rate (ETR), Non-Photochemical Quenching, (NPQ), total chlorophyll, and meiotic index presented significantly lower values under ALAN, primarily, but not exclusively, in Cladocopium cell cultures. The findings also showed that diverse Symbiodiniaceae types have different photo-physiology and photosynthesis performances under ALAN. We believe that our results sound an alarm for the probable detrimental effects of an increasing sensory pollutant, ALAN, on the eco-physiology of symbiotic corals. The results of this study point to the potential effects of ALAN on other organisms in marine ecosystem such as fish, zooplankton, and phytoplankton in which their biorhythms is entrained by natural light and dark cycles.